Analysis of Food and Beverage Cost Control in WBS - N G A P P Rahmayanti; I M Sudana; I M D J Sulastra (Journal of Applied Sciences in Accounting, Finance, and Tax, 2020)
This study aims to determine (1) the factors that cause the difference of food and beverage costs between actual costs and standard costs, (2) control of food and beverage costs at WBS. The data used in this study were food and beverage reconciliation reports, recipe cards and SOP (Standard Operating Procedures) on the functions involved in controlling food and beverage costs. The measuring instruments used to conduct this study were cost of food and beverage sold, food and beverage cost percentage, food and beverage cost percentage difference, and SOP on the functions involved in controlling food and beverage costs. The results showed that (1) the occurrence of food and beverage cost differences during these periods were due to an increase in gross cost of food sold and gross cost of beverage sold; (2) food and beverage controls is basically adequate, but is less consistent in applying the applicable SOP so that problems were found such as purchases from non-suppliers due to lack of food stocks, received goods with quantities that didn’t match the market list order or purchase order, and the implementation of standard recipe and standard portion size is not optimal in the preparation of food and beverage.